Pengaruh Pelatihan terhadap Kinerja Karyawan pada PT. Jaya Kencana Jakarta - Alexsander, Diki; Lubis, Andriani (Sekolah Menengah Kejuruan (SMK) Pustek, 2025)
In the face of increasingly competitive business environments, organizations must enhance employee productivity through effective training programs. This study aims to examine the influence of training on employee performance at PT. Jaya Kencana Jakarta, where a gap persists between training implementation and actual performance improvement. A quantitative approach was applied, involving a survey of 50 permanent employees selected through total sampling. Data were collected using structured questionnaires and analyzed using simple linear regression, Pearson correlation, and coefficient of determination, assisted by SPSS version 27. The findings reveal that training significantly affects employee performance. The regression analysis indicates a positive linear relationship, with a regression coefficient of 0.560 and a significance level of 0.000. The correlation coefficient of 0.702 suggests a strong, positive relationship between training and performance, while the determination coefficient shows that training contributes 49.3% to performance variance. These results highlight the importance of well-designed and targeted training in enhancing workforce efficiency and effectiveness. The study provides practical insights for HR managers to improve training strategies and emphasizes the need for future research to consider additional variables such as motivation or leadership to gain a more comprehensive understanding of performance drivers.